Sleep status and influencing factors of primary and secondary school teachers in China - Xue, Lian; Chen, Ying; Wang, Huan; Peng, Yin; Li, Yujiao; Wang, Yi (Frontiers in Public Health, 2025)
ObjectiveTo investigate the sleep status and influencing factors affecting primary and secondary school teachers, this study aims to provide insights for enhancing their sleep quality and establishing effective mechanisms for sleep management and intervention.MethodsA cross-sectional survey was conducted using cluster sampling to recruit 225 teachers from 58 primary and secondary schools in Mianyang, Sichuan Province, China. Questionnaires included demographic data, Pittsburgh Sleep Quality Index (PSQI), the Dysfunctional Beliefs and Attitudes about Sleep-16 (DBAS-16), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and a work stress questionnaire for primary and secondary school teachers. Descriptive statistics were employed to characterize the sleep status, independent sample t-tests, Spearman’s correlation analysis, and analysis of variance (ANOVA) were used for univariate analyses of sleep quality, and multiple linear regression was performed to model the influencing factors of sleep quality.ResultsThe PSQI score was 8.29 ± 4.58, DBAS-16 score 40.63 ± 12.14, GAD-7 score 7.01 ± 5.21, PHQ-9 score 9.05 ± 6.46, and work stress questionnaire score 67.51 ± 34.04 (standardized to 1.88 ± 0.95). Univariate analysis showed significant differences in sleep quality among teachers with different teaching durations, salary satisfaction, anxiety, depression, work stress, and sleep beliefs/attitudes (all p < 0.05). Multiple linear regression analysis identified that teaching duration, anxiety, depression, and work stress were influencing factors of sleep quality (all p < 0.05).ConclusionThe sleep quality of primary and secondary school teachers was generally poor (69.3%), with high detection rates of anxiety (65.3%) and depression (74.7%). Depression (β = 0.303, p < 0.001) and anxiety (β = 0.208, p = 0.016) showed strong positive predictive power for sleep quality, indicating that more severe emotional problems were associated with poorer sleep.